(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The article discusses conceptual approaches to restoring the competitiveness of territorial communities and regions. The main reasons for the decrease in competitiveness are analyzed and the factors affecting the effectiveness of their restoration are determined. Special attention is paid to ensuring sustainable development and improving the quality of life of the population in the regions. The article analyzes such approaches to restoring competitiveness as attracting investments, developing technologies and innovations, creating a favorable business environment, improving the management efficiency of territorial communities and regions, as well as providing social support to the population. The article found that the competitiveness of territories is a key component for ensuring sustainable economic development and ensuring a high level of the population’s quality of life. The article considers such approaches to restoring competitiveness as development of innovations, transformation of territories, attraction of investments, development of human potential, etc. The analysis and justification of various approaches to restoring the competitiveness of territorial communities and regions was carried out. The question of the impact of political, economic and social factors on the development of regions and communities was considered, as well as the role of management and strategic planning in ensuring sustainable development was analyzed. A complex of problems leading to a general decrease in the level of competitiveness of territorial communities and regions has been studied, and on the basis of this, conceptual approaches to their restoration have been proposed. In the context of the modern economy, competitiveness is an important success factor for the development of various territories. However, due to the various challenges facing regions, restoring competitiveness can be a difficult task. The essence of various conceptual approaches to restoring the competitiveness of territories, in particular, innovative, ecological, socially oriented and others, is considered. The main measures that must be implemented to ensure the restoration of the competitiveness of territorial communities have been determined.